POTENTIAL OF OZONE WATER TO REDUCE THE SEVERITY OF ORAL MUCOSITIS IN PATIENTS POST HEAD AND NECK RADIOTHERAPY - Annisa Gustiasti Arumsadu; Niluh Ringga Woroprobosari; Rina Kartika Sari; Rochman Mujayanto (Faculty of Dentistry, Universitas Islam Sultan Agung, 2021)
Background: Cancer is the second leading cause of death in the world after heart disease. One type of cancer, namely head and neck cancer, can be treated with head and neck radiotherapy. Continuous radiotherapy will cause an increase in oxidative stress and free radicals and damage to the oral mucosa, one of which is oral mucositis. Giving ozone water can help reduce the degree of oral mucositis in patients. Ozone water itself has several beneficial effects such as antioxidant, anti-inflammatory, and antimicrobial. The purpose of this study was to determine the potential of ozone water in reducing the severity of oral mucositis in patients after head and neck radiotherapy.Method: Gargling treatment using ozone water in a ratio of 2:3 for 1 minute with 4 repetitions for 2 weeks showed a significant reduction in pain. Ozone used in gas or liquid form for more than 5 minutes has the potential to cause side effects on the duration of inflammation and for gas can cause infection in the respiratory tract.Conclusion: The conclusion of this review is that the administration of ozone water with a concentration of 2-4 ppm for approximately 5 minutes has the potential to cure oral mucositis due to head and neck radiotherapy